Governing [through] Autonomy. The Moral and Legal Limits of “Soft Paternalism” - Fateh-Moghadam, Bijan (Ethical theory and moral practice, 2014)
Legal restrictions of the right to self-determination increasingly pretend to be compatible with the liberal concept of autonomy: they act upon a ‘soft’ or autonomy-orientated paternalistic rationale. Conventional liberal critique of paternalism turns out to be insensitive to the intricate normative problems following from ‘soft’ or ‘libertarian’ paternalism. In fact, these autonomy-oriented forms of paternalism could actually be even more problematic and may infringe liberty rights even more intensely than hard paternalistic regulation. This paper contributes to the systematic differentiation of soft and hard paternalism by discussing the (legal) concept of autonomy and elaborates the moral and legal limits of autonomy-orientated paternalism.